EKSTRAK DAUN SAWO (Manilkara zapota L) SEBAGAI INHIBITOR TERHADAP LAJU KOROSI BAJA AISI 1018 DALAM MEDIUM KOROSIF NaCl 3% - Riski Wulan Sari; Ediman Ginting Suka; Pulung Karo Karo (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2022)
This research aims to determine the effectiveness of sapodilla leaf extract (Manilkara zapota L) as inhibitor on AISI steel in corrosive medium NaCl 3 %. Specifically, the purpose of this research is to know the effect of the addition of 0%, 2% and 4% inhibitor concentration of sapodilla leaf extract and 3 days, 6 days and 9 days to the corrosion rate. To find out the corrosion rate resulted by weight reduction method with an inhibitor efficiency value of 59,2%. The x-ray diffraction (XRD) results show that the phase formed is pure Fe phase. The results of scanning electron microscopy (SEM) show the presence of lumps on steel surfaces of various sizes which are the product of corrosion. This is reinforced by the results of energy dispersive spectroscopy (EDS) which shows that the increasing number of lumps on the steel surface leaves fewer Fe elements.